FAKTOR FAKTOR PENYEBAB TERJADINYA KREDIT MACET UED-SP (USAHA EKONOMI DESA SIMPAN PINJAM) DI KECAMATAN SENTAJO RAYA - Ningrum Agustia Widya; Azlina Nur; Mela Fito Nanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to test the influences: Internal factors, external factorsagainstnonperforming loans UED-SP (save the Village Economy Business loan) indistrict Sentajo Kingdom. The sample in this research totalled 63 Respondents. Method ofdetermination of the sample using the method of purposive sampling with certain criteria.Technique of data analysis in this study using multiple linear regression, t-Test and testthe assumptions of normality tests include classic, multikolonearitas, heteroskedastisitasand autocorrelation data management using program SPSS version 25.0 softwere.Fromthe test results indicates that the variable Internal factors (X 1) effect on bad credit (Y),variable external factors (X 2) effect on bad credit (Y)Keywords : Internal Factors, External Factors